Biomineralization in the Tissues of the Human Body - Lukiienko, Natalia (European Journal of Scientific Exploration, 2018)
In this scientific work we consider such a phenomenon of the formation and development of living organisms as biological mineralization. This process accompanies living organisms for many millions of years. With this process, not only people, but also other animals and living beings develop and evolve. Years ago the formation of the first biominerals has begun. These are some of the main components that make everything alive. The first biominals were formed in the distant Precambrian periods, with the help of matrix and cellular organisms, as well as water. We will consider the process of mineralization in the human body, in particular, as a phenomenon that allows the formation of tissues, and also leads to pathological consequences.